Dollarization: Concepts and Implications for Monetary and Exchange Rate Policy in the Philippines - Josef T. Yap (Philippine Institute for Development Studies (PIDS), 2001)
Dollarization denotes the use of a foreign currency in any of its three functions: unit of account, means of exchange and store of value. In terms of the latter aspect, dollarization has been increasing in the Philippines. Empirical tests that confirm the significance of dollarization are generally flawed but what is more important is to determine the impact of dollarization on the efficacy of monetary policy and the choice of exchange rate regime. Full dollarization or official dollarization has both its costs and benefits but this is not a viable option for the Philippines at the moment.
Keywords: 330; dollarization; Währungssubstitution; Münzgewinn; Wechselkurssystem; Philippinen